Malaysia : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This report provides the analysis of IMF's projections and estimates for Malaysia on gross domestic product by expenditures and production at constant prices; industrial production index; labor market developments; composition of investment and saving in current prices; consumer price index and producer price index; federal government revenues and grants; economic and functional classification of federal government expenditure and net lending; federal government operations and fiscal operations, operations of statutory bodies, state, and local governments; general government operations; monetary survey; banking survey; balance of payments; international reserves during 1995-99; interbank swap transactions, 1995-2000, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet